Calendrical variations in Second Temple Judaism: new perspectives on the "Date of the Last Supper" debate - Saulnier, Stéphane (Journal for the study of Judaism, 2012)
Preliminary Material -- Introduction -- I. The Date of the Last Supper: Annie Jaubert’s Theory Revisited -- II. The Cycle of Festivals and the Seasons in the Hebrew Bible -- III. The Cycle of Festivals and the Seasons in the Book of Jubilees -- IV. The Cycle of Festivals in the Dead Sea Scrolls -- V. The Cycle of Festivals in Other Relevant Jewish Sources -- VI. Calendrical Issues in the Book of Luminaries (1 Enoch 72–82) -- VII. The Calendrical Documents from Qumran -- VIII. Conclusions -- Appendix: The 364-Day Year, the Lunar Cycle, and the Triennial Cycle -- Bibliography -- Index of Subjects -- Index of Modern Authors -- Index of Scriptures and Other Ancient Writings.